The Identification and Quantitative Analysis of Unusual Keto-Carotenoids in Ripe Fruits of Maclura tricuspidate and Its Potential as a Valuable Source of Cryptocapsin - Jong-Kuk Kim; Dae-Woon Kim; Yoseph Asmelash Gebru; Han-Seok Choi; Young-Hoi Kim; Myung-Kon Kim (Molecules, 2022)
Ripe fruits of Maclura tricuspidata (MT) are used as food material and a natural colorant in Korea. Although MT fruits have a deep red color due to carotenoid-like pigments, their chemical nature has not been explored in detail so far. The present study aimed at elucidating the chemical structures and composition of carotenoids in MT fruits and changes at different maturity stages. Two carotenoids from saponified MT fruit extract were isolated using repeated silica gel column chromatography. Based on interpretations of spectroscopic data, these compounds were determined as keto-carotenoids, i.e., capsanthin (3,3′-dihydroxy-β,κ-caroten-6′-one) and cryptocapsin (3′-hydroxy-β,κ-caroten-6’-one), and the contents of individual carotenoids were quantified with HPLC based on calibration curves obtained from authentic standards. The contents of capsanthin and cryptocapsin in the sample of saponified MT fruits were 57.65 ± 1.97 µg/g and 171.66 ± 4.85 μg/g as dry weight base (dw). The majority of these keto-carotenoids in the MT fruits were present in esterified forms with lauric, myristic or palmitic acid rather than in their free forms. The results also showed that esterification of these compounds occurred starting from early stage (yellow-brownish stage) of maturation. Considering the high cryptocapsin content, MT fruits can be applied as a potentially valuable source of cryptocapsin for food and medicinal application as well as a source of provitamin A.